Vilniaus ir Dysnos apskričių baudžiavinių ūkių raidos XIX a. vidurys statistinė analizė: koreliacinė ir regresinė analizė - Pamerneckis, Stasys (Lietuvos istorijos studijos, 1997)
This article is written with the application of correlation-regression and factorial statistical models for researching corvee-peasant farms. In the richest peasant farms of the third group most intensive correlations connections were formed.Factorial analysis was based on two main factors-general economical level and provision with fodder and food. Factorial indexation of all peasant farms on factorial weights reflects comparatively high typological community of corvee-peasant farms in the middle of the 19th century.